Surface brillouin scattering (SBS) study of photoelastic properties of transparent materials - Dube, Hlosani Ngqongqotshi (My University, 2019)
Brillouin spectroscopy (BS) was employed to investigate the elastic constants of bulk (strontium uoride (SrF2) and thin lm (silicon carbide (SiC)) materials. Results of volume scattering experiments on SrF2 provided an excellent baseline study of bulk modes which proved invaluable in the analysis of the scattering pro le generated by the complex system of a-SiC lms grown on transparent substrates in this unique study. In this study, SrF2, which has continued to be of technological interest because of its fast ion conductivity in the vicinity of its melting point, has its elastic constants measured using Brillouin scattering. Independent elastic constants of SrF2 were determined from SBS measurements and were found to be c11 116 GPa, c12 45 GPa and c44 33 GPa. These values agree very well with those in literature. SiC continues to receive intensive interest due to its applicability in micro electromechanical systems (MEMS) operating in harsh environments. In this study, amorphous thin lms of SiC were deposited on di erent substrates using magnetron sputtering.The elastic constants of SiC thin lms deposited on sapphire and silicon were obtained by inverse extraction of elastic constants using elastodynamic Green's function applied to the phonon dispersion curves. The lms were characterized using microscopic and x-ray techniques, amongst others. The elastic constants of the amorphous lms on sapphire were obtained as c11 250 GPa and c44 74 GPa and for amorphous lms on silicon substrate were c11 160 GPa and c44 100 GPa. Some very interesting anomalous loading e ects of the di erent substrates were observed. The analysis of the dispersion curves of thin SiC/substrate combinations characterized by sti ness e ects showed the appearance of anomalous behavior in a range of small normalized thickness. Thus, the evolution of the dispersion curves are not only in uenced by velocity but also by densities of the respective lm/substrate materials.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in ful llment of the academic requirements for the degree of Master of Science. Johannesburg, February 2019